The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1039/c3ib20273a
|View full text |Cite
|
Sign up to set email alerts
|

A model of membrane contraction predicting initiation and completion of bacterial cell division

Abstract: Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes the work of researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable the material made available in WRAP has been checked for eligibility before being made available.Copies of full items can be used for personal research or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…We have developed a model of this key phase of cell division 7 and showed that the results are consistent with the division behaviour observed following the loss of expression of FtsA or ZipA, two components of the Escherichia coli divisome complex. This strongly suggests that the simulation model is a reliable tool to probe the early stages of cytokinesis which critically depend on the Z-ring and its membrane interactions.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…We have developed a model of this key phase of cell division 7 and showed that the results are consistent with the division behaviour observed following the loss of expression of FtsA or ZipA, two components of the Escherichia coli divisome complex. This strongly suggests that the simulation model is a reliable tool to probe the early stages of cytokinesis which critically depend on the Z-ring and its membrane interactions.…”
Section: Introductionsupporting
confidence: 58%
“…The model has been implemented in Mathematica 8 as detailed in our previous paper. 7 In this paper we present the predicted wild-type behaviour and the predicted effects of various perturbations to key biochemical parameters and contrast those predictions with available experimental data.…”
Section: Model Overviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Prior to cell division, the cell elongates to approximately twice its original length while its genetic material is replicated. Once this is complete, filamentous temperature sensitive (Fts) proteins, chief among which is FtsZ, assemble to form the cell division apparatus (divisome) by polymerizing and thus forming the socalled Z-ring, which localises to the middle of the cell [37][38][39] . New cell envelope material is synthesised and the two chromosomes are pulled apart.…”
Section: Cell Division and Growthmentioning
confidence: 99%
“…One good example is the model of bacterial metabolism, where the state variables are metabolite concentrations, gene expression levels, transcription factor activities, metabolic fluxes, and biomass concentration 25 . However, in many cases the aim is not to describe the whole organism but instead to focus on specific subsystems of the cell, such as the assembly of the Z-ring 37 , or the electron transport chains of mitochondria 51 and purple non-sulfur bacteria 52 . Depending on the specific properties of the given biological network under consideration, different formalisms can be employed to simulate its dynamic behaviour.…”
Section: Contemporary Approaches: Microscopic Modelsmentioning
confidence: 99%